Análise de concentração e rivalidade no mercado de aviação civil no Brasil: um cenário hipotético de duopólio - Pereira, Renan Pegas (Universidade Federal de São Carlos, 2025)
The present study aims to analyze market concentration and indications of rivalry in the Brazilian civil aviation passenger transport sector, considering a hypothetical merger scenario between Gol and Azul in the main domestic air routes. To achieve this, market share data, the Herfindahl Hirschman Index (HHI), and the relative market share instability test were applied to the most demanded routes in Brazil between January 2021 and July 2024. Among them, the key routes analyzed include Rio de Janeiro – São Paulo (SBRJ – SBSP; Santos Dumont and Congonhas airports), São Paulo – Brasília (SBSP – SBBR; Congonhas and Presidente Juscelino Kubitschek airports), and Recife – Guarulhos (SBRF – SBGR; Recife/Guararapes International and Guarulhos airports). In the current scenario, high levels of concentration are observed. In the hypothetical merger scenario, concentration increases significantly, establishing a dominant position for the new company and practically reducing the market to a duopoly. The ADF tests indicate instability in market share participation in the hypothetical scenario, which may suggest rivalry. The results emphasize the need for a thorough and careful competitive assessment in the event of a merger or acquisition in the sector.
Analysis of concentration and rivalry in the Brazilian civil aviation market: a hypothetical duopoly scenario
Keywords: Aviação Civil Brasileira; Concentração de Mercado; Fusões e Aquisições; Rivalidade; Rotas Aéreas Domésticas; Brazilian Civil Aviation; Market Concentration; Mergers and Acquisitions; Rivalry; Domestic Air Routes; CIENCIAS SOCIAIS APLICADAS::ECONOMIA